Article Edukasi Manajemen Stres Pada Anggota Keluarga Dengan Masalah Hipertensi - Lisdahayati Lisdahayati; Saprianto Saprianto; Zanzibar Zanzibar; Nelly Rustiati; Muhammad Yuda Saputra (NHM PRESS, 2023)
Stress is one of the causes of increased high blood pressure. Continued stress causes blood pressure to remain high so that hypertension is increasingly out of control. Stress management is one of the factors controlling hypertension. This study aims to find out the description of Stress Management Education for Family Members who Suffer from Hypertension. The research used in the case study uses a descriptive method with a nursing process approach. The subjects in the case study were 2 client families suffering from hypertension at the Tanjung Agung Health Center. Research data collection was carried out directly to clients by observing the client's general condition and to find out changes in client behavior using several instruments in the form of checklists, questionnaires, and interviews. The findings from this case study show that after providing education about stress management, the client's knowledge about stress management and hypertension has increased. Education about stress is very important for families who have family members with hypertension. By understanding this relationship, families can take steps to manage stress and prevent negative effects on family members who suffer from hypertension. Researchers suggest the importance of stress education for family members who experience hypertension in the implementation of family nursing care so that it can improve the quality of interventions and subsequent health programs.